2020
DOI: 10.1002/agr.21683
|View full text |Cite
|
Sign up to set email alerts
|

Influence of food safety standards on trade: Evidence from the pistachio sector

Abstract: This paper analyses the influence of food safety standards related to aflatoxin contamination on the pistachio trade of the world's two leading pistachio producers (the United States and Iran) during the period 1996–2014. Using diverse econometric procedures, the estimation of extended gravity models shows that both countries benefit from stricter food safety standards imposed by importing countries. The results also show that US exports are not negatively affected by the distance from the importer (higher dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, Hu and others (2023), Jin and others (2023), and Rabadán and Triguero (2021) point out that certifications can represent a disadvantage for small farmers and small businesses because many retailers require their suppliers to be certified in a recognized standard, which represents a cost if desired. Enter export markets, which reduces their production volume and increases the possibility of exiting the market.…”
Section: Quality and Organizational Innovation: Competitiveness Tools...mentioning
confidence: 99%
“…On the other hand, Hu and others (2023), Jin and others (2023), and Rabadán and Triguero (2021) point out that certifications can represent a disadvantage for small farmers and small businesses because many retailers require their suppliers to be certified in a recognized standard, which represents a cost if desired. Enter export markets, which reduces their production volume and increases the possibility of exiting the market.…”
Section: Quality and Organizational Innovation: Competitiveness Tools...mentioning
confidence: 99%
“…TBTs formulated by Japan, the United States, the EU, and South Korea have positive effects on the development of China’s agricultural export trade. Rabadán and Triguero found that the United States and Iran benefit from stricter food safety standards imposed by importing countries in the trade of pistachios 18 . Song and Zang (2016) considered the time dimension and the time point dimension.…”
Section: Literature Reviewmentioning
confidence: 99%